AGING BEYOND NUMBERS: THE ASSOCIATION BETWEEN POPULATION AGING AND COST-RELATED HEALTHCARE ACCESS IN OECD COUNTRIES - Zeliha Köse; Kenan Kıbıcı (Gazi Sağlık Bilimleri Dergisi, 2026)
Background: This study examines the association between population aging and cost-related healthcare access across OECD countries. Methods: An unbalanced panel dataset comprising 102 country-year observations from 15 OECD countries over the period 2000–2023 was analyzed. Fixed-effects and random-effects models with standard errors clustered at the country level were estimated. Based on the Hausman test, the random-effects model was retained as the preferred specification. Results: In the preferred random-effects model, population aging was not significantly associated with consultations skipped due to cost (β = −0.155, 95% CI: −0.800 to 0.489, p = 0.637). None of the explanatory variables was statistically significant, and the model was not jointly significant (Wald χ²(5) = 6.91, p = 0.227). Although life expectancy was positively associated with consultations skipped due to cost in the fixed-effects model (β = 1.035, p = 0.038), this association was not significant in the preferred random-effects model (β = 0.414, p = 0.255). Conclusion: The findings indicate that population aging alone does not explain cost-related healthcare access across the selected OECD countries. Further research incorporating additional health-system and contextual indicators may provide a more comprehensive understanding of healthcare accessibility.